The Life of Islamic Boarding School Students as a Model of Reinforcing the Eroded Nationalism - Abbas, Ersis Warmansyah; Mutiani, Syaharuddin; Hidayat Putra, Muhammad Adhitya; Jumriani,; Noor Handy, Muhammad Rezky (International Journal of Psychosocial Rehabilitation, 2020)
Known as Kota Santri - the city where many religious apprentice live, Martapura, South Kalimantan Indonesia houses 9,232 santri in Darussalam Martapura Islamic life experience school. Darussalam has 2 (two) quarters with a limit of 70 rooms, every one of which has 4 (four) santris. Subsequently, most understudies live in residences or houses on the banks of the Martapura River. This examination plans to depict the life of understudies at the Martapura River utilizing qualitative methods which find that the experience of understudies depends on freedom in building singular capacities that at the same time construct a public activity to accomplish shared objectives. From one perspective, understudies are required to satisfy their own lives so their instruction in Islamic boarding school known as pesantren is effective and produce a social cognizance among understudies and with the network then again so it isn't disposed of from public activity that underpins the achievement of training in pesantren. In regular daily existence, understudies are found in building freedom and public activity actualized in the act of social qualities, to be specific: strict, patriotism, honesty, autonomy and participation. The estimations of public activity of santri on the Martapura River banks can be utilized as a learning asset for sociologies study, particularly in building autonomy and public activity.